Structures of complexes formed by H5 influenza hemagglutinin with a potent broadly neutralizing human monoclonal antibody - Xiong, Xiaoli (Proc Natl Acad Sci U S A, 2015)
H5N1 avian influenza viruses remain a threat to public health mainly because they can cause severe infections in humans. These viruses are widespread in birds, and they vary in antigenicity forming three major clades and numerous antigenic variants. The most important features of the human monoclonal antibody FLD194 studied here are its broad specificity for all major clades of H5 influenza HAs, its high affinity, and its ability to block virus infection, in vitro and in vivo. As a consequence, this antibody may be suitable for anti-H5 therapy and as a component of stockpiles, together with other antiviral agents, for health authorities to use if an appropriate vaccine was not available. Our mutation and structural analyses indicate that the antibody recognizes a relatively conserved site near the membrane distal tip of HA, near to, but distinct from, the receptor-binding site. Our analyses also suggest that the mechanism of infectivity neutralization involves prevention of receptor recognition as a result of steric hindrance by the Fc part of the antibody. Structural analyses by EM indicate that three Fab fragments are bound to each HA trimer. The structure revealed by X-ray crystallography is of an HA monomer bound by one Fab. The monomer has some similarities to HA in the fusion pH conformation, and the monomer’s formation, which results from the presence of isopropanol in the crystallization solvent, contributes to considerations of the process of change in conformation required for membrane fusion.